Oxygen and nitrogen co-doped porous carbons with finely-layered schistose structure for high-rate-performance supercapacitors. (October 2017) - Tang, Chenggui; Liu, Yijiang; Yang, Duanguang; Yang, Mei; Li, Huaming
Abstract: Heteroatom-doped porous carbons have currently been regarded as the promising materials for supercapacitors because of their outstanding contributions in Faradaic capacitance and electrolyte accessibility. In the present study, O/N co-doped porous carbons have been prepared by carbonization of ammonium citrate single precursor followed by KOH activation. The as-synthesized carbon (ACA-800) has a finely-layered schistose architecture together with a high surface O and N-containing functionalities (6.82 at.% O and 1.37 at.% N), a high micropore surface area (1522 m 2  g −1 ) and a balanced mesopore surface area (1138 m 2  g −1 ). Due to their synergistic effects, the ACA-800 electrode displays high-rate capacitive performance with specific capacitance of 297 F g −1  at 100 A g −1, at least 85% of its capacitance (349 F g −1 ) at 1 A g −1 . Moreover, symmetric supercapacitor assembled with such ACA-800 exhibits high energy density of 25.5 W h kg −1  at 923 W kg −1 as well as excellent cycling stability (only 4% of capacitance loss after 10000 cycles with a cell voltage of 1.8 V at a current load of 2 A g −1 ). Considering the global abundance and low price of ammonium citrate, it can serve as a novel precursor for the mass production of O/N-enriched porous carbons for advanced supercapacitors. Graphical abstract: